2015
DOI: 10.1371/journal.pone.0140524
|View full text |Cite
|
Sign up to set email alerts
|

W3 Is a New Wax Locus That Is Essential for Biosynthesis of β-Diketone, Development of Glaucousness, and Reduction of Cuticle Permeability in Common Wheat

Abstract: The cuticle plays important roles in plant development, growth and defense against biotic and abiotic attacks. Crystallized epicuticular wax, the outermost layer of cuticle, is visible as white-bluish glaucousness. In crops like barley and wheat, glaucousness is trait of adaption to the dry and hot cultivation conditions, and hentriacontane-14,16-dione (β-diketone) and its hydroxy derivatives are the major and unique components of cuticular wax in the upper parts of adult plants. But their biosynthetic pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 66 publications
2
37
0
3
Order By: Relevance
“…The wheat waxes comprise various classes of VLC aliphatics including β‐diketones, alkanes, and primary alcohols, similar to many other monocots and dicots. Recent reports revealed that β‐diketone formation largely depends on genes clustered in the W1, W2, and W3 loci residing on different chromosomes in separate subgenomes (Adamski et al, ; Tsunewaki & Ebana, ; Zhang et al, ). Other studies showed that at least eight functional FAR enzymes are involved in formation of VLC primary alcohols, all with different expression profiles (Chai et al, ; Wang, et al, 2015b; Wang, et al, 2015c; Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The wheat waxes comprise various classes of VLC aliphatics including β‐diketones, alkanes, and primary alcohols, similar to many other monocots and dicots. Recent reports revealed that β‐diketone formation largely depends on genes clustered in the W1, W2, and W3 loci residing on different chromosomes in separate subgenomes (Adamski et al, ; Tsunewaki & Ebana, ; Zhang et al, ). Other studies showed that at least eight functional FAR enzymes are involved in formation of VLC primary alcohols, all with different expression profiles (Chai et al, ; Wang, et al, 2015b; Wang, et al, 2015c; Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that leaf cuticular wax is associated with plant drought tolerance in many species, such as Arabidopsis , cotton and wheat (Bondada et al, 1996; Kosma et al, 2009; Zhang et al, 2015). And Chatterton et al (1975) reported that sorghum yield was associated with cuticular wax; however, wheat drought tolerance conferred by cuticular wax has rarely been studied with NILs in wheat (Uddin and Marshall, 1988; Araus et al, 1991; Zhang et al, 2005; Cameron et al, 2006; Kim et al, 2007; Yang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…To date, six genes controlling wax biosynthesis have been reported and are located on the following wheat chromosomes: W1 and IW1 on 2BS, W2 and IW2 on 2DS, W3 on 2BS, and IW3 on 1BS (Tsunewaki and Ebana, 1999; Adamski et al, 2013; Wu et al, 2013; Wang et al, 2014a; Zhang et al, 2015), but little is known about the functions of these genes. Previous studies showed that leaf cuticular wax can protect the plants against abiotic and biotic stresses, such as drought, UV and the wheat grain aphid (Blum and Ebercon, 1981; Shepherd and Wynne Griffiths, 2006; Wójcicka, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, both CYP96B30 and WES were found to be highly coexpressed with the three cluster genes DMP, DMH, and DMC. Recently, Zhang et al (2015) identified the W3 locus, which is linked to W1, and suggested its involvement in b-diketone biosynthesis. Given the complexity of the W1/Iw1 region, W3 might be included in this interval.…”
Section: Multiple Genes Rather Than a Single One Encoding A Multifuncmentioning
confidence: 99%
“…In particular, many Poaceae species (including wheat [Triticum spp], barley [Hordeum vulgare], rye [Secale cereale], and oat [Avena sativa]) produce very-long-chain b-diketones with characteristic structures likely formed along pathways different from those leading to more ubiquitous wax compounds (Supplemental Figure 1). Despite many years of research on b-diketone biosynthesis, particularly in barley and wheat (von Wettstein-Knowles, 1976, 1995von Wettstein-Knowles and Søgaard, 1980;Adamski et al, 2013;Zhang et al, 2013Zhang et al, , 2015, the genes and enzymes involved remain to be discovered.…”
Section: Introductionmentioning
confidence: 99%